International human rights : text and materials - Alston, Philip; Goodman, Ryan; Steiner, Henry J. (2013)
"The successor to International human rights in context : law, politics and morals."
Human rights concepts and discourse -- The human rights regime : background and birth -- Civil and political rights -- Economic and social rights -- National security, terrorism and the law of armed conflict -- Rights or duties as organizing concepts -- Conflict in culture, tradition and practices : challenges to universalism -- The United Nations human rights system -- Treaty bodies : the ICCPR Human Rights Committee -- International human rights fact-finding -- Regional arrangements -- Vertical interpenetration : international human rights law within states' legal and political orders -- Horizontal interpenetration : transnational influence and enforcement of human rights -- Measuring and evaluating human rights performance -- Massive human rights tragedies : prosecutions and truth commissions -- Non-state actors and human rights -- Human rights, development and climate change.
"The successor to International human rights in context: law, politics and morals."
Includes bibliographical references and index.
Keywords: UN System; International Covenant on Civil and Political Rights -- (1966); Human rights; Human rights -- Moral and ethical aspects; Droits de l'homme.; Droit international; Organisations internationales; Human rights; Human rights -- Moral and ethical aspects; HUMAN RIGHTS; CIVIL AND POLITICAL RIGHTS; ECONOMIC, SOCIAL AND CULTURAL RIGHTS; INTERNATIONAL INSTRUMENTS; NATIONAL SECURITY; TERRORISM; HUMAN RIGHTS VIOLATIONS; TRUTH COMMISSIONS; NON-STATE ACTORS; Derechos humanos; Derechos humanos